2021
DOI: 10.3399/bjgpo.2021.0106
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic prescribing for acute infections in synchronous telehealth consultations: a systematic review and meta-analysis

Abstract: BackgroundAntibiotic prescribing is a major concern that contributes to the problem of antibiotic resistance.AimTo assess the effect on antibiotic prescribing in primary care of telehealth (TH) consultations compared to face-to-face (F2F).Design & settingSystematic review and meta-analysis of adult or paediatric patients with a history of a community acquired acute infection (respiratory, urinary, or skin and soft tissue). We included studies that compared synchronous TH consultations (phone or video based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…found that the impact of telehealth consultations on antibiotic prescribing varied between conditions. 40 That study highlighted there was a significant decrease in antibiotic prescribing for acute rhinosinusitis during telehealth consultations. However, they observed an increase in antibiotic prescribing for acute otitis media during telehealth consultations.…”
Section: Discussionmentioning
confidence: 99%
“…found that the impact of telehealth consultations on antibiotic prescribing varied between conditions. 40 That study highlighted there was a significant decrease in antibiotic prescribing for acute rhinosinusitis during telehealth consultations. However, they observed an increase in antibiotic prescribing for acute otitis media during telehealth consultations.…”
Section: Discussionmentioning
confidence: 99%
“…The process of retrieving the literature and selecting the articles included in this review has been illustrated in a flow diagram (Figure 1) which complied with the RIGHT checklist for reporting a clinical practice review. Of the six publications included within this review, five were review papers (10)(11)(12)(13)(14) and one was an observational study (15). The authors of the five review papers had evaluated current literature on the effectiveness of telehealth for a patient population group with lower urinary tract symptoms and UTI and expressed the significance of implementing telehealth during the COVID-19 pandemic.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Telemedicine has been regarded as an essential method for patient review and follow-up during the COVID-19 pandemic particularly for LUTS cases secondary to UTI (12). Somani et al (15) lay emphasis the impact of virtual urological services being the optimal method of minimizing service disruption and Bakhit et al has shown that telehealth treatment prescribing for UTI does not differ from face to face, and is an effective method of distanced management of the disease (14). Although telehealth has evolved and is a convenient method of managing a population with chronic UTI, challenges may be present in a population who are not digitally competent which is evident through the lack of digital skills, comprehension of how to use health technologies and technophobia (10,12).…”
Section: The Effectiveness Of Telehealthmentioning
confidence: 99%
“…8 This includes evidence that the shift to telemedicine is associated with increased antibiotic prescribing. 9 Antibiotic monitoring by the US Centers for Disease Control and Prevention (CDC) showed an increase in antibiotic use as clinicians face uncertainty as to whether a respiratory infection is due to SARS-CoV-2 or another cause. 10 A review of data from COVID-19 cases, mostly in Asia, found that more than 70% of patients received antimicrobial treatment.…”
Section: Antimicrobial Resistancementioning
confidence: 99%